Engineering of Mesoscale Pores in Balancing Mass Loading and Rate Capability of Hematite Films for Electrochemical Capacitors. Issue 26 (6th August 2018) - Song, Yu; Liu, Tianyu; Li, Mingyang; Yao, Bin; Kou, Tianyi; Feng, Dongyang; Wang, Fuxin; Tong, Yexiang; Liu, Xiao‐Xia; Li, Yat
Abstract: Design and synthesis of metal oxide‐based pseudocapacitive materials to simultaneously achieve high mass loading (e.g., up to 10 mg cm −2 ) and excellent rate capability for electrochemical capacitors is a long‐lasting challenge. These two characteristics are usually mutually exclusive due to the poor ion diffusion kinetics of most metal oxides. Here, a glucose‐assisted hydrothermal method to prepare thick hematite film (>1 µm) with engineerable mesopore size through controlled variation of glucose concentration is demonstrated. The capability of controlling the size of mesopores offers a unique opportunity to investigate for the first time the interplay between mesopore size and electrochemical performance of hematite films. The hematite film with an average mesopore size of 3 nm at an ultrahigh loading of 10 mg cm −2 exhibits an areal capacitance of 1502 mF cm −2 at 1 mA cm −2, and retains 871.2 mF cm −2 at 50 mA cm −2 . Such performance, to the best of the authors' knowledge, is at the top of the reported hematite electrodes with comparable or even lower mass loadings. The strategy demonstrated herein may be extended to fabricate diverse types of mesoporous metal oxide architectures with improved ion diffusion kinetics, which is critical for a broad range of devices for energy storage and conversion. Abstract : A glucose‐assisted hydrothermal synthetic method to prepare thick hematite film (>1 µm) with engineerable mesopore size through controlled variation of the glucose concentration is demonstrated. The controllability of the mesopore size offers a unique opportunity to investigate for the first time the interplay between mesopore size and the electrochemical performance of hematite films.